LOGIC MODELING: A TOOL FOR TEACHING PRACTICE EVALUATION. - Alter, Catherine; Murty, Susan (Journal of Social Work Education)
The article presents an assessment of logic modeling as a tool for teaching evaluation skills in practice, research and policy courses in social work education. There are several benefits of using logic models. If properly used, logic models help students understand and avoid the common pitfalls of evaluation. Logic models can be seen as maps with guide posts that help keep the intervention or program on course. A logic model can also become a common cognitive structure, conceptual map of intention that has many uses throughout the life of the intervention. Perhaps the most important reason for completing a logic model before an intervention starts, is to be able to use it as a framework for evaluation. The three evaluation approaches for which logic models have been used as framework, which are resource evaluation, process evaluation and outcome evaluation, have been discussed in the article. Logic model as framework for clarifying focus of different evaluation approaches, has been discussed with the aid of a diagram. It describes the resource evaluation for economic self-sufficiency program (ESP) through a table-based study.